Application of fluent tp predict combustion performance for pure propane - Muhammad Aminuddin, Abd Rahman (2008)
Computational Fluid Dynamic (CFD) is a used tool in optimizing propane burner for emissions issues and to study combustions characteristics of flame temperature and flame velocity in furnace system. Using CFD simulation, cost and time can reduce in development new furnace and burner. Studies are aimed at improving combustion performance with reduce pollutant emissions. Also focus on the combustion patterns in the form of measured contours of temperature and species concentrations. Pure propane used as a fuel in this research. Before doing computer simulation, several experiments were running first. Only the best data will choose. This data is use in boundary setting when doing simulation process. In experimental work, practical combustor C492 gas burner is used. The data from the experimental work will analyze and compare to get a constant and stable data. For simulation work 2D design for practical combustor was done in Gambit software. In this software, the design was mesh and export to Fluent 6.3. Fluent 6.3 is one of CFD software that uses to study combustion and flow characteristics. The result from experimental work and computer simulation then compared. The comparison shows in the Table 4.2 in term of percentage differences. Best result depends on small percentage between this two data.